2020
DOI: 10.1111/raq.12419
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsiales‐like organisms in bivalves and marine gastropods: a review

Abstract: Rickettsiales‐like organisms (RLOs) are intracellular bacteria that have been reported to be symbionts of over 60 species of bivalves and marine gastropod molluscs of aquaculture importance around the world. Morphologically, some of these prokaryotes are similar to bacteria from the order Rickettsiales, and in most cases, they form intracytoplasmic inclusions similar to those observed in bacteria of the family Anaplasmataceae. Genetically, only Candidatus Xenohaliotis californiensis (CXc), a parasite of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 84 publications
(300 reference statements)
0
7
0
Order By: Relevance
“…Endozoicomonas strains have been isolated from corals, and their metabolic potential was inferred from derived genomic studies on the isolates and metagenomes assembled from culture-independent studies, suggesting integrated metabolic links facilitating nutrient acquisition and provision and therefore potentially important roles in host health (14,(21)(22)(23)(24). Some Endozoicomonas have been reported to locate within aggregates of the coral tissues (14) and other marine invertebrates (10,11,13), although other bacterial taxa including Rickettsiales (Alphaproteobacteria) and Chlamydia (Chlamydiae) have also been reported to form aggregations in corals (23,25) and mollusks (26,27); hence, these coral-associated microbial aggregates (CAMAs) could be constructed with polymorphous types of bacteria (28,29). However, the spatial localization of these symbionts is still largely overlooked, particularly with respect to individual phylotypes and populations across bacterial lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Endozoicomonas strains have been isolated from corals, and their metabolic potential was inferred from derived genomic studies on the isolates and metagenomes assembled from culture-independent studies, suggesting integrated metabolic links facilitating nutrient acquisition and provision and therefore potentially important roles in host health (14,(21)(22)(23)(24). Some Endozoicomonas have been reported to locate within aggregates of the coral tissues (14) and other marine invertebrates (10,11,13), although other bacterial taxa including Rickettsiales (Alphaproteobacteria) and Chlamydia (Chlamydiae) have also been reported to form aggregations in corals (23,25) and mollusks (26,27); hence, these coral-associated microbial aggregates (CAMAs) could be constructed with polymorphous types of bacteria (28,29). However, the spatial localization of these symbionts is still largely overlooked, particularly with respect to individual phylotypes and populations across bacterial lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that the microbiota in bivalves can be influenced by local factors [8,9] and can contribute beneficial functions to the host, such as the improvement of digestive tract development, the increase in an immune response against pathogen attack, and the provision of essential nutrients (e.g., vitamins, enzymes, and fatty acids) [10,11]. In contrast, studies have also revealed the occurrence of pathogenic bacteria in the microbiota, including both zoonotic pathogens (e.g., Vibrio splendidus, Vibrio aestuariuanus, and Nocardia crassostreae) and human pathogens (e.g., Vibrio parahaemolyticus and Vibrio vulnificus) [12][13][14][15]. Similarly, studies have also linked shifts in microbiota composition to bivalve mass mortality events [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of rickettsia infections in abalone Haliotis spp. it has been shown that temperature, hostsusceptibility and pathogen-specificity can affect the growth of the IMCs and subsequently cause disease and mortality (Cruz-Flores and Cáceres-Martínez, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the vast majority of IMC infecting mollusks remains unclassified, despite some of them being associated with population declines. This information is essential to establish the type of symbiosis they maintain with their host (mutualisms, commensalism or parasitism) and whether they can act as true pathogens and from there to determine the necessity of implementing control measures in aquaculture (Cruz-Flores and Cáceres-Martínez, 2020). In the present study, the microbial diversity associated to IMCs infecting economically important marine molluskan species was interrogated by a 16S rRNA gene amplicon sequencing and phylogenetic analysis approach, through international collaboration, to progress in the molecular identification of IMCs infecting mollusks.…”
Section: Introductionmentioning
confidence: 99%